Gender-Dependent Effects of Early Maternal Separation and Variable Chronic Stress on Vasopressinergic Activity and Glucocorticoid Receptor Expression in Adult Rats - Renard, Georgina Maria (2010)
The aim of the present study was to investigate the influence of early maternal separation on Fos, arginine vasopressin (AVP) and glucocorticoid receptor (GR) expression in the medial parvocellular portion of the paraventricular hypothalamic nucleus (PaMP), and GR expression in the hippocampus of adult male and female rats subjected to variable chronic stress (VCS). Male and female Wistar rats were isolated 4.5 h daily, during the first 3 weeks of life. At 48 days of age, the rats were exposed to VCS. Nonmaternally separated (NMS) females had a higher number of activated AVP neurons than NMS male rats. Maternally separated (MS) females subjected to VCS also showed a higher number of Fos/AVP double-labeled neurons than males with the same treatment. Males and females subjected to early maternal separation and VCS, compared with the MS animals, showed a decrease in the expression of GR in the PaMP. As regards GR expression in the hippocampus, MS animals subjected to VCS as adults, both males and females, showed an increase in GR expression in the subfields CA1, CA2 and CA3. The increase in AVP-immunoreactive neurons coexpressing Fos in response to stress in females exposed to early maternal separation suggests that perhaps early life stress results in a more reactive neuroendocrine stress response in females. Furthermore, our results demonstrate that the different anatomical levels of the hypothalamic-pituitary-adrenal axis have different roles related to its stress response and support the evidence of regional specificity in GR regulation.